2016
DOI: 10.1021/acs.jnatprod.5b01096
|View full text |Cite
|
Sign up to set email alerts
|

A 2S Albumin from the Seed Cake of Ricinus communis Inhibits Trypsin and Has Strong Antibacterial Activity against Human Pathogenic Bacteria

Abstract: Hospital-acquired infections caused by antibiotic-resistant bacteria threaten the lives of many citizens all over the world. Discovery of new agents to hinder bacterial development would have a significant impact on the treatment of infections. Here, the purification and characterization of Rc-2S-Alb, a protein that belongs to the 2S albumin family, from Ricinus communis seed cake, are reported. Rc-2S-Alb was purified after protein extraction with Tris-HCl buffer, pH 7.5, fractionation by ammonium sulfate (50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Additionally, the sole positive charge (bold underlined), shown to be essential for activity in the present study, is surrounded by multiple Gln or Asn residues at the C-terminus. Interestingly, this overall arrangement is shared with certain other plant defence-related proteins including the flocculating cationic peptide from Moringa oleifera seed shown to damage bacterial membranes via a membrane fusion mechanism 75 , and a 2S albumin from Ricinus communis which causes leakage of bacterial cells postulated to result from magainin-like pore formation 76 (see Table 1 ). A motif query (avoiding redundancy) of the RCSB Protein Data Bank for the H3 C-terminal 6-residue motif [N/Q]-[N/Q]-[N/Q]-[A/L/I/V]-[K/R]-[N/Q] yielded a total of just 28 proteins, all lipid-interacting or surface-active (see Supplementary Table S1 for a listing of these matches).…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the sole positive charge (bold underlined), shown to be essential for activity in the present study, is surrounded by multiple Gln or Asn residues at the C-terminus. Interestingly, this overall arrangement is shared with certain other plant defence-related proteins including the flocculating cationic peptide from Moringa oleifera seed shown to damage bacterial membranes via a membrane fusion mechanism 75 , and a 2S albumin from Ricinus communis which causes leakage of bacterial cells postulated to result from magainin-like pore formation 76 (see Table 1 ). A motif query (avoiding redundancy) of the RCSB Protein Data Bank for the H3 C-terminal 6-residue motif [N/Q]-[N/Q]-[N/Q]-[A/L/I/V]-[K/R]-[N/Q] yielded a total of just 28 proteins, all lipid-interacting or surface-active (see Supplementary Table S1 for a listing of these matches).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, our research group characterized and evaluated the antimicrobial activity of many SAMPs against bacteria and yeasts pathogenic to humans 13–15 . For example, Dias et al 14 reported that Rc Alb‐PepII (SLRGCC) is a small (637.77 Da), positively charged (+1), and slightly (pI 7.80) basic peptide with hydrophobicity of 50%, derived from an antimicrobial 2S albumin purified from Ricinus communis seed cake, 16 and a potent antimicrobial peptide against C. parapsilosis and Klebsiella pneumoniae . Lopes et al 15 reported that a synthetic peptide derived from a thaumatin protein induces apoptosis in C. albicans .…”
Section: Introductionmentioning
confidence: 99%
“…Trichophyton mentagrophytes microconidia were analysed by AFM, as previously described by Souza et al 20 The samples were treated with peptides, collected and washed as done for the SEM analysis. After that, the protocol for AFM was followed.…”
Section: Methodsmentioning
confidence: 99%